Expressão gênica de interferon-gama, fator de necrose tumoral alfa e interleucinas 2 e 5 no baço de gatos naturalmente infectados por Leishmania spp: Karina Yukie Hirata. - - Hirata, Karina Yukie [UNESP] (2015)
Considering the complexity of the immune response against Leishmania spp. infection in different species and the lack of clinical signs in the majority of cats with visceral leishmaniasis, this study aimed to evaluate the gene expression of some cytokines involved in cellular (IFN-, TNF α, IL-2) and humoral (IL-5) immune response by real-time PCR, on spleen samples from 12 cats naturally infected by Leishmania spp., comparing to the immune response of four healthy cats; and to verify the correlation between the parasite load in the bone marrow and the gene expression of cytokines in the spleen of infected animals. An increase of 1.53 times in IFN- gene expression was observed in infected cats when compared to healthy cats (p=0.0005). Statistically significant differences were not observed in gene expression of the cytokines evaluated between infected and healthy cats (TNF-α p=0.4203, IL-2 p=0.1968, IL-5 p=0.6390). Correlation was not observed between the parasite load in the bone marrow and the gene expression of cytokines in the spleen of cats infected by Leishmania spp. (IFN- p = 0.1570; TNF- p = 0.5702; IL-2 p = 0.6081; IL-5 p = 0.2329). These results suggest that IFN- may play an important role in the protective mechanisms against feline leishmaniasis